Cytosolic 5′-Nucleotidase II Is a Sensor of Energy Charge and Oxidative Stress: A Possible Function as Metabolic Regulator - Rossana Pesi; Simone Allegrini; Francesco Balestri; Mercedes Garcia-Gil; Federico Cividini; Laura Colombaioni; Lars Petter Jordheim; Marcella Camici; Maria Grazia Tozzi (Cells, 2021)
Cytosolic 5′-nucleotidase II (NT5C2) is a highly regulated enzyme involved in the maintenance of intracellular purine and the pyrimidine compound pool. It dephosphorylates mainly IMP and GMP but is also active on AMP. This enzyme is highly expressed in tumors, and its activity correlates with a high rate of proliferation. In this paper, we show that the recombinant purified NT5C2, in the presence of a physiological concentration of the inhibitor inorganic phosphate, is very sensitive to changes in the adenylate energy charge, especially from 0.4 to 0.9. The enzyme appears to be very sensitive to pro-oxidant conditions; in this regard, the possible involvement of a disulphide bridge (C175-C547) was investigated by using a C547A mutant NT5C2. Two cultured cell models were used to further assess the sensitivity of the enzyme to oxidative stress conditions. NT5C2, differently from other enzyme activities, was inactivated and not rescued by dithiothreitol in a astrocytoma cell line (ADF) incubated with hydrogen peroxide. The incubation of a human lung carcinoma cell line (A549) with 2-deoxyglucose lowered the cell energy charge and impaired the interaction of NT5C2 with the ice protease-activating factor (IPAF), a protein involved in innate immunity and inflammation.